(untitled) (Italian Journal of Public Health, 2012)
Background: despite growing interest in Internet addiction disorder (Iad) among the high school population, very little is known about the potential risks of the use of the Internet for university students. The present survey aimed to collect information on Internet usage patterns in a group of Italian university students. Methods: the sample comprised 600 Italian university students enrolled in various faculties, in two different universities: catania (n=300; 150 males and 150 females) and Palermo (n=300; 150 males and 150 females). The diagnostic Questionnaire for Iad based on 8 criteria was used to categorize the Internet users. In order to better describe students’ Internet usage patterns, 4 other criteria were added. chi-square test (P<0.05) was applied to examine differences between the two groups of students (catania versus Palermo), and for comparisons between male and female students. Results: respondents were ‘minimal’ (82.5%) or ‘moderate’ (17.5%) Internet users. none of the enrolled university students met the criteria of definite Iad, although a fairly high level of at-risk Internet attitudes and behaviors was found. Finally, some gender differences in Internet attitudes and behaviors were found. Conclusions: the implications drawn from this study, including the adequacy of the available measurement instruments for Iad, are discussed....